2021
DOI: 10.3390/diseases9040081
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Electro-Hyperthermic (mEHT) Treatment in the Therapy of Inoperable Pancreatic Cancer Patients—A Single-Center Case-Control Study

Abstract: Our present oncological treatment arsenal has limited treatment options for pancreatic ductal adenocarcinoma (PDAC). Extended reviews have shown the benefits of hyperthermia for PDAC, supporting the perspectives with the improvements of the treatment possibilities. METHODS: A retrospective single-center case-control study was conducted with the inclusion of 78 inoperable PDAC patients. Age-, sex-, chemotherapy-, stage-, and ascites formation-matched patients were assigned to two equal groups based on the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Retrospective observational study with mEHT-treated and untreated arms for advanced pancreatic cancer showed that mEHT was successfully applicable for various pancreatic tumors [ 75 ], and also for the specially nonresectable tumors compared to PSM [ 76 ], as well as relative long overall survival; Table 5 .…”
Section: Clinical Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…Retrospective observational study with mEHT-treated and untreated arms for advanced pancreatic cancer showed that mEHT was successfully applicable for various pancreatic tumors [ 75 ], and also for the specially nonresectable tumors compared to PSM [ 76 ], as well as relative long overall survival; Table 5 .…”
Section: Clinical Validationmentioning
confidence: 99%
“… Comparison of the survival studies of advanced pancreas carcinomas ① [ 75 ] ( n = 106), ② [ 99 ] ( n = 25), ③ [ 120 ] ( n = 99), ④ [ 76 ] ( n = 78), ⑤ [ 120 ] ( n = 34), ⑥ SEER (NCI, USA) data from [ 99 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations